The characteristics and antigenic properties of recently emerged subclade 3C.3a and 3C.2a human influenza A(H3N2) viruses passaged in MDCK cells. Issue 3 (28th February 2017) - Lin, Yipu; Wharton, Stephen A.; Whittaker, Lynne; Dai, Mian; Ermetal, Burcu; Lo, Janice; Pontoriero, Andrea; Baumeister, Elsa; Daniels, Rodney S.; McCauley, John W.
Abstract : Background: Two new subclades of influenza A(H3N2) viruses became prominent during the 2014‐2015 Northern Hemisphere influenza season. The HA glycoproteins of these viruses showed sequence changes previously associated with alterations in receptor‐binding properties. To address how these changes influence virus propagation, viruses were isolated and propagated in conventional MDCK cells and MDCK‐SIAT1 cells, cells with enhanced expression of the human receptor for the virus, and analysed at each passage. Methods: Gene sequence analysis was undertaken as virus was passaged in conventional MDCK cells and MDCK‐SIAT1 cells. Alterations in receptor recognition associated with passage of virus were examined by haemagglutination assays using red blood cells from guinea pigs, turkeys and humans. Microneutralisation assays were performed to determine how passage‐acquired amino acid substitutions and polymorphisms affected virus antigenicity. Results: Viruses were able to infect MDCK‐SIAT1 cells more efficiently than conventional MDCK cells. Viruses of both the 3C.2a and 3C.3a subclades showed greater sequence change on passage in conventional MDCK cells than in MDCK‐SIAT1 cells, with amino acid substitutions being seen in both HA and NA glycoproteins. However, virus passage in MDCK‐SIAT1 cells at low inoculum dilutions showed reducing infectivity on continued passage. Conclusions: Current H3N2 viruses should be cultured in the MDCK‐SIAT1 cell line to maintain faithful replication of the virus, and at an appropriate multiplicity of infection to retain infectivity.